(untitled) (Iranian Journal of Kidney Diseases, 2016)
Introduction. Kidney disease increases the risk of cardiovascular disease. The corollary of that observation should be that cardiovascular disease would not only increase the risk of kidney dysfunction, but also cause kidney damage, a concept not previously proposed. Materials and Methods. Hemodynamic response to a graded exercise stress test was measured in 70 candidates to evaluate the association of heart rate and blood pressure change, heart rate reserve, chronotropic incompetence (percentage of achievement of maximal predicted heart rate), and circulatory power with development of kidney failure (glomerular filtration rate < 30 mL/min/1.73 m2) during 123 months of follow-up period. Results. Kidney failure was more likely to develop in patients with lower heart rate change, heart rate reserve, percentage of achievement of maximal predicted heart rate, and circulatory power (P = .002, P = .01, P = .02, and P = .008, respectively), even after adjustment for age, resting pulse pressure, hypertension, diabetes mellitus, and exercise test result (hazard ratios, 5.9, 2.9, 3.3, and 2.9, respectively). A resting pulse pressure of 60 mm Hg and higher was accompanied by 7.4 times (95% confidence interval, 1.8 to 30.9) greater risk of developing kidney failure, independent of age and resting systolic blood pressure (P = .006). Conclusions. Hemodynamic responses to a standard graded exercise stress test independently predicted the development of kidney failure. Also, arterial stiffness (represented by resting pulse pressure) could be a factor linking ventricular and kidney function. Early diagnosis of kidney disease should include a cardiovascular assessment and vice versa.